In the shade we stumble: Theatre laboratory as a living archive - Kuhlmann, Annelis (Mimesis Journal, 2013)
The moment of presence in the art of acting in the contemporary theatre is in the postdramatic theatre confronted with a redefinition of mimesis. Very often one can witness how contemporary performances draw upon historical events and perspectives. This problem can be seen in a frame of re-enacting techniques and traditions, questioning the archives of the performing art as well as the performing of the archives as the embodied memories of the actor. This double sided sword is here seen in the context of the theatre laboratory tradition. A theoretical and analytical perspective from Diana Taylor’s The Archive and the Repertoire (Durham and London 2003) is used in order to emphasize the physical nature of the art of acting as a strategic tool for the heritage of a theatre laboratory. Here, this focus takes its point of departure from the articulation of practitioners’ creative working processes, and how the professional language has become manifest in itself. The major example for article is the theatre laboratory tradition at Odin Teatret. In this context several of the actors – especially the actresses – have documented their articulation of creative working processes in a written communicable form, which makes it interesting anew to re-question the mimetic dimension of the performing archive of this theatre laboratory.